Comparative Analysis of Amylase Enzyme Produced by Aspergillus niger Using Rice and Maize Bran as Substrates (Asian Journal of Plant Biology, 2023)
Amylase is used in the degradation of starch-containing materials into its simpler constituents. This study was aimed at comparing amylase production by Aspergillus niger isolated from different sources on different varieties of rice and maize bran. Different strains of A. niger were isolated from different sources and were identified using cultural, morphological and molecular characteristics. A. niger USGB:1024 isolated from soil obtained from a maize mill and A. niger BGSU:17-00030 isolated from spoiled tomato were used for amylase enzyme production as both gave positive results during screening. Amylase enzyme was produced using 15g of substrates, temperature 30 C, pH 6 and inoculum density of 1 ×106. A. niger USGB:1024 was found to produce an amylase enzyme with the highest activity (3.15±0.1 IU) on Chinese rice bran at fermentation day 5. A. niger BGSU:17-00030 also produced amylase enzyme with the highest activity (1.46±0.01 IU) on Chinese rice bran at 5 days of fermentation. The result has shown that A. niger USGB:1024 produced amylase enzyme with the highest activity than A. niger BGSU:17-00030.
Keywords: Aspergillus niger; Miaze bran; Amylase; Soil; Rice bran